The effect of dietary zinc level and source on yearling bull growth and fertility - Arthington, J.D.; Johnson, K.R.; Corah, L.R.; Willms, C.L.; Hill, D.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To study the effect of dietary zinc level and source on bull growth and fertility, 325 yearling Angus bulls were allotted by weight into six pens (three pens of heavy and three pens of lightweight bulls). The three supplemental zinc (Zn) treatments were 1) 40 ppm inorganic Zn all supplied by Zn sulfate (ZnI); 2) 40 ppm Zn with 1/3 supplied by Zn proteinate and 2/3 supplied by Zn sulfate (ZnPI); and 3) 60 ppm ZnI all supplied by Zn sulfate (ZnHi). Initial and final liver biopsies (10 per pen) were collected and analyzed for zinc concentration. Individual weights and scrotal circumferences also were recorded at the start and conclusion of the trial. Bull s intended for public sale (n=167) had their semen collected and evaluated for motility and morphological abnormalities. Bulls with percent normal sperm cell counts of less than 70% or with motility scores less than fair (motility scores = poor, fair, good, very good) were considered classification deferred (CD). Following 126 days of treatment, ZnHi bulls had a greater (P=.058) percent change in liver Zn concentration than ZnI, but similar increases to ZnPI. No difference s in bull ADG or percent change in scrotal circumference were detected. ZnPI and ZnHi bulls had a higher (P<.05) percent of normal sperm cells than ZnI bulls. ZnPI and ZnHi treatments had fewer (P<.05) CD bulls than ZnI. In all fertility measures observed , bulls receiving the Zn proteinate/Zn sulfate combination at 40 ppm had improved semen quality when compared to bulls supplemented with 40 ppm Zn sulfate.
Keywords: Beef; Zinc; Bull; Growth; Fertility